Calcium dependence of serotonin-induced changes in rabbit ileal electrolyte transport. - Donowitz, M (1980)
These studies describe the calcium dependence of the serotonin-induced changes in active electrolyte transport in rabbit ileum in vitro. In the presence of a standard calcium concentration (1.2 mM) in the serosal bathing fluid, serosal serotonin caused a transient increase in short-circuit current and a prolonged decrease in net Na and Cl fluxes. Removing calcium from the serosal (no calcium plus 1 mM EGTA) but not the mucosal bathing fluid inhibited the serotoin-induced increase in ileal short-circuit current, and also completely blocked the serotonin effects on net Na and net Cl fluxes. This inhibition was rapidly reversed by readding calcium. Removing serosal calcium did not inhibit all active electrolyte transport processes, as the effect of a maximum concentration of theophylline (10 mM) was not altered. Similarly, d,l-verapamil, a calcium channel blocker, inhibited the serotonin-induced changes in short-circuit current and in net Na and net Cl fluxes, but did not alter the theophylline effects. In contrast, d-verapamil, a stereoisomer which does not block calcium channels, did not inhibit the serotonin-induced changes. The calcium dependence of these serotonin effects was associated with increased uptake of 45Ca into rabbit ileum, including increaed 45Ca uptake from the serosal surface. Serotonin also increased the rate of 45Ca efflux from rabbit ileum into a calcium-free solution, compatible with serotonin increasing the ileal plasma membrane permeability to calcium. It is postulated that serotonin affects active intestinal electrolyte transport by a mechanism dependent on serosal but not mucosal calcium that involves an increase in the intestinal plasma membrane permeability to calcium, and perhaps an increase in intracellular calcium.